INSTILLING ISLAMIC EDUCATION STRATEGY FOR CHILDREN IN INDONESIA AT DIGITAL ERA - Izattul Isnaini (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2019)
The world experiences massive fundamental changes as a result of the digital era. Not only in the field of technology and communication, changes also occur in children's daily behavior. Bad various shows can be accessed easily by children and can cause negative behavioral effects on children. Supervision is needed from parents to guide children for negative impacts can be minimized. The problem that occurs is most parents are confused about what should be done to prepare children in facing their environment. Instilling religious values from an early age is expected to be one of the strongholds for children to face changes. Pendidikan Agama Islam (PAI) is one of the most important pilar of education. A child’s character will build well, if it is started from cultivating religious sense of students.